(untitled) (Herald of the National Children’s Medical Center, 2025)
One of the key pathogenetic mechanisms of acute renal failure (ARF) in children is a hypersympathotonic reaction that causes peripheral vasospasm, including the renal vessels. This accompanies the centralization of blood circulation in conditions of hypovolemia and other forms of stress. The study of circadian rhythms of heart rate (HR) in the context of acute renal failure is especially important for understanding adaptive and decompensatory mechanisms in pediatric intensive care.